2012
DOI: 10.1159/000336060
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Age for 3-Year Continuous Behavioral Obesity Treatment Success and Dropout Rate

Abstract: Objective: To assess whether first year weight loss, age, and socioeconomic background correlate with the success rate of continuous long-term behavioral obesity treatment. Methods: In a 3-year longitudinal study, obese children (n = 684) were divided into three groups based on age at the start of treatment, age 6–9 years, 10–13 years, and 14–16 years. Results: The mean BMI standard deviation score (BMI-SDS) decline was age-dependent (p = 0.001), independently of adjustment for missing data: –1.8 BMI-SDS units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 71 publications
3
49
0
1
Order By: Relevance
“…Conventional treatments for obesity in adolescents have a generally poor outcome 6 and new treatment alternatives are needed. A recent randomized controlled trial demonstrated that laparoscopic gastric banding is superior to conventional therapy in adolescents recruited directly from the community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conventional treatments for obesity in adolescents have a generally poor outcome 6 and new treatment alternatives are needed. A recent randomized controlled trial demonstrated that laparoscopic gastric banding is superior to conventional therapy in adolescents recruited directly from the community.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment mainly consists of individualized or family-based counseling and cognitive behavior therapy concerning diet and physical activity. 6 Low-calorie diets and drugs (metformin, orlistat or sibutramin) were prescribed if found clinically indicated by the treating pediatrician. This treatment continued in the conventional treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions involving lifestyle and dietary approaches, even when considered successful, achieve only modest weight reductions, often in a limited proportion of patients [65,[67][68][69][70][71]. Although wide-ranging and accessible to many, such programs are offset by inevitable relapse in most individuals.…”
Section: Surgery Is the Only Effective Treatment For Obesitymentioning
confidence: 99%